Mitigation and Adaptation Strategies for Global Change - Mitigation and Adaptation Strategies for Global Change (Springer Nature, 2026)
Mitigation and Adaptation Strategies for Global Change publishes significant research from a broad range of environmental, socio-economic, policy, and technology strategies to address the challenges of global change - in particular climate and environmental change. The journal provides a forum to encourage conceptualization, critical examinations, and debates regarding effective strategic responses and options to mitigate and to adapt to global changes impacting climate stability, ecological systems, and human habitats and security. In particular, it aims to invite integrated views and solutions, to advance understanding of multiple perspectives onto these challenges, including the interrelation and interaction among the strategic responses and options.
FI 0.6
Q3
Keywords: Earth; Space & Environmental Sciences; Atmospheric Sciences; Ciencias atmosféricas; Acuerdos transformativos; Transformative agreements; Medio ambiente; Economía; Energía